“Where is the mother’s instinct?” : a case study on how motherhood is learned through the practice of Chinese confinement. - Lee, Wei Qi. (2010)
Motherhood has always been treated as an essential phase of life in the female life course, so much so that it has been seen as biological by many around the world. But in recent years, studies on how motherhood is a social construct, and thus a learned process, have started to gain precedence within the field of study. In this study, I aim to explore how Chinese first-time mothers experience motherhood as a learning process in the context of confinement. Through the use of qualitative research methods, I will find out how these mothers learn, adapt and familiarize themselves into this phase of life. Findings have shown that women are often place into the role of a mother unknowingly, leading them to have the assumption that motherhood is an innate process. But after experiencing motherhood itself, they have found a disjuncture between these encounters and the expectations. Hence, through the confinement period, they seek to solve this crisis, and in the process, learn how to be a mother.